Influence of mineral fertilizers on the quality of winter wheat grain on typical chernozem in the Left-Bank Forest-Steppe - Lisovyi, M.V.; Nikonenko, V.M.; Karatsiuba О.V.; Slidenko О.I.; Shimel, V.V. (AgroChemistry and Soil Science, 2021)
The goal was to study the effect of certain types of mineral fertilizers (N, P, K) and their paired compounds (NP, NK, PK) on the protein and gluten content in the grain of winter wheat on chernozem typical (Haplic Chernozem (Profundihumic)). The research was carried out in the conditions of a field stationary experiment which was laid down in the experimental farm of the NSC "Institute for Soil Science and Agrochemistry Research named after O. N. Sokolovsky" in the Kharkiv region. Eight variants with the following norms of fertilizers were studied for winter wheat: 1 – without fertilizers (control); 2 – N60; 3 – P120; 4 – K90; 5 – N60P120; 6 – N60K90; 7 – P120K90; 8 – N60P120K90. The effectiveness of fertilizers was reseached on two agrophones - natural and aftereffect of fertilizers (240 t/ha for crop rotation). The content of protein and gluten in wheat grain was determined on the Spectran-119M. On typical chernozem of the Forest-Steppe of the left-bank high application of nitrogen and phosphorus fertilizers in norm N60P120 provides the content of protein in grain of winter wheat at the level of 12,9 – 14,7 % that corresponds to the 1st and 2nd classes of quality of grain according to the National standard (DSTU 3768 : 2010). The gluten content ranges from 23.6 to 25.0 %, which corresponds to the 2nd class of grain quality of winter wheat.